Delayed luminescence: an experimental protocol for Chinese herbal medicines. (28th January 2016) - Sun, Mengmeng; van Wijk, Roeland; van Wijk, Eduard; Wang, Mei; van Wietmarschen, Herman; Hankemeier, Thomas; van der Greef, Jan
Abstract: In Chinese medicine, raw herbal materials are used in processed and unprocessed forms aiming to meet the different requirements of clinical practice. To assure the chemical quality and therapeutic properties of the herbs, fast and integrated systematic assays are required. So far, such assays have not been established. Delayed luminescence (DL) refers to a decaying long‐term ultraweak photon emission after exposure to light. Its decay kinetics under certain conditions may be a sensitive indicator reflecting the internal structural and chemical/physiological state of a biological system. DL measurements have been used in many applications for quality control. However, relatively little research has been reported on dried plant material such as Chinese herbs. The objective of the present study is to establish a protocol for direct and rapid DL measurements of dried Chinese herbal materials, including the determination of the dependence on: (a) the optimal excitation time utilizing a white light source; (b) the optimal size of the grinded herbal particle; and (c) the humidity conditions before and during measurement. Results indicate that stable and reproducible curves of DL photon emission depend mainly on the water content of herbal materials. To investigate the application of the established DL measurement protocol, non‐processed and processed Aconitum ( Aconitum carmichaelii Debx.), wild and cultivated rhubarb ( Rheum palmatum L.) and ginseng ( Panax ginseng C.A.Mey) of different ages were measured using DL. The results suggest that DL technology is a potential tool for assessment of dried Chinese herb qualities. The results warrant a further exploration of this technique in relation to therapeutic properties of the herbs. Copyright © 2016 John Wiley & Sons, Ltd.